GENDER SEGREGATION OF HEALTH MANAGERS IN DISTRICT HEALTH OFFICERS IN INDONESIA - Kambarwati Nur Marwah Shofi; Nuzulul Kusuma Putri (The Indonesian Journal of Public Health, 2023)
Introduction: Women dominate  Indonesia's health system but  there is no clear evidence how this is represented equally in the decision-making process. Globally, the healthcare system is challenged by gender segregation of health managerial position. Aims: This study  is to explain the findings  regarding patterns of male or female dominance in the particular division of the district health office. Methods: This study was an original research discussing gender segregation of male and female dominance as health managers in district health office. We listed the characteristics of health managers in two provinces with different kinship system. These characteristics were then compared with several gender segregation patterns i.e. work area; position requirement; dominant task coordination; workplace; emergency possibility; budget; percentage of the female manager based on matriarchy and patriarchy background. Result: Female managers of a matriarchal background dominate in General Secretariat (63.4%). Public Health and Community Empowerment (62.5%) and Healthcare Services (80%). A significant portion of men of a patriarchy background shows that men are dominating in two divisions, Disease Prevention and Control (57.8%) and Health Services (55.3%). The study proved the existence of the dominance of one gender in a specific job. This indicated the existence of gender segregation in the healthcare system. Conclusion: Female managers tend to be placed in domestic organization affairs while the male managers are generally responsible for interorganizational affairs, including jobs with high emergency responses.